Fuzzy model of sustainable development with the inclusion of financial variables - Zioło, Magdalena; Spoz, Anna; Bąk, Iwona; Oesterreich, Maciej (Technological and Economic Development of Economy, 2022)
The aim of the article was to build a model based on fuzzy logic describing the level of sustainable development for the individual EU Member States in 2009–2019 and to conduct fuzzy simulations as a result of which scenarios for the prediction of sustainable development acknowledging financial variables (the share of environmental taxes, a deficit, a debt). The original research approach is expressed by including fuzzy models in the analysis of the level of sustainable development with the inclusion of financial variables. The Netherlands achieved the highest value (the highest level of sustainable development) (0.571). Slovenia (0.564) and Denmark (0.559) came second and third. The lowest average value (the lowest level of sustainable development) was recorded for Slovakia (0.423). After 10 years there are evident changes in the distribution of individual typological groups. In 2019, the countries belonging to the first and second typological groups were located primarily in the northern and central Europe. The scenario analysis showed that in the case of most countries, if the analyzed variables remained at the maximum or minimum level throughout the analyzed period, it would not significantly affect the assessment of their level of sustainable development, their ranking positions, and inclusion into typological groups. First published online 03 August 2022